Raising production and productivity of rice-based cropping systems through Rice Crop Manager in the Philippines - CGIAR Research Program on Rice (2019)
Rice Crop Manager (RCM) is a decision-support tool designed for use by agricultural extension workers. It is accessible online on personal computers, tablets, or smartphones. In the Philippines, more than 2.1 million recommendations have been generated for farmers from 2014 to 2019 and monitoring, evaluation and learning from 2018 revealed that 27% of farmers have adopted the RCM recommendations across all regions.